ADSORPTION OF METHYL VIOLET DYE BY THERMALLY MODIFIED CEIBA PENTANDRA SAWDUST (Universitas Negeri Semarang, 2017)
The disposal of synthetic dyes into the environment is an important source of water pollution. Methyl violet, a typical cationic dye has been widely applied in industries, including textile industries.The dye causes the bad effect to the aquatic life because these compounds are quite stable and have low biodegradability. It presents an aesthetic problem and reduces photosynthetic activity. In this study, modified ceiba pentandra sawdust has been investigated as an adsorbent for the removal of methyl violet dye from aqueous solutions. The modification has been carried out using heating treatment at 110oC and 200oC for one hour. The FTIR spectra of raw and modified Ceiba pentandra sawdust were recorded using an FTIR technique (Perkin Elmer, USA) by the KBr pellet method. The spectrum was scanned in the range of 400 to 4000 cm-1 wavenumbers. The photomicrography of the exterior surface of raw and modified ceiba pentandra sawdust was obtained by SEM (JEOL, Japan). Batch studies were performed to address various experimental parameters including pH, contact time, and initial concentration for the removal of this dye. The results show that heating treatment increases the amount of methyl violet adsorbed. Effective pH for methyl violet adsorption was 7. A greater percentage of dye was removed with a decrease in the initial concentration of dye. Quasi-equilibrium reached in 30 min. Equilibrium isotherms were analysed by Langmuir and Freundlich isotherm equations. Freundlich equation is found to best represent the equilibrium data for methyl violet-modified kapok sawdust system.